2009
DOI: 10.1111/j.1365-2516.2009.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia in Spain

Abstract: To determine the prevalence of haemophilia A and B and their complications in Spain, and to characterize the health care network providing support to haemophiliac patients. The study examines clinical and genetic characteristics, treatment options, and complications observed during the course of the disease. Cross-sectional multi-centre study. The study population were patients with HA and HB in active follow-up at any Spanish hospital by December 2006. We studied 2400 haemophiliacs, 2081 (86.7%) HA and 319 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
60
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 34 publications
11
60
0
5
Order By: Relevance
“…1 A recent Spanish epidemiological study has estimated that 2518 individuals have hemophilia A and 387 have hemophilia B. 2,3 The estimated prevalence of hemophilia, therefore, would be $1 in 7857 males. This estimate is lower than that derived from the extrapolation of data from Canada (1 in 5811) or the United Kingdom (1 in 5143) and similar to that reported from European countries like Sweden (1 in 7374) or Poland (1 in 8492).…”
Section: Care For Patients With Bleeding Disorders In Spainmentioning
confidence: 99%
“…1 A recent Spanish epidemiological study has estimated that 2518 individuals have hemophilia A and 387 have hemophilia B. 2,3 The estimated prevalence of hemophilia, therefore, would be $1 in 7857 males. This estimate is lower than that derived from the extrapolation of data from Canada (1 in 5811) or the United Kingdom (1 in 5143) and similar to that reported from European countries like Sweden (1 in 7374) or Poland (1 in 8492).…”
Section: Care For Patients With Bleeding Disorders In Spainmentioning
confidence: 99%
“…Actualmente la esperanza de vida del hemofílico se asemeja a la de la población general y la edad media del paciente hemofílico se sitúa alrededor de los 30 años. Un elevado porcentaje de los pacientes hemofílicos graves presentan lesiones del aparato locomotor y, para centrar la importancia de las necesidades de terapia física, concretamente en España, el 12,4% de los pacientes menores de 14 años presenta artropatía 3 ( fig. 1).…”
Section: Conceptos Generales De La Hemofiliaunclassified
“…Los sangrados intraarticulares o hemartrosis son la manifestación clínica más frecuente y más conocida de la hemofilia, tanto grave como moderada, representando el 65-80% de todas las hemorragias 9,10 . Las articulaciones afectadas en mayor proporción son las rodillas, los codos y los tobillos, que suponen el 60-80% de todas las hemartrosis 3,11 . Si estas hemorragias no son tratadas o son mal tratadas, se produce a largo plazo un daño articular irreversible que conduce a la artropatía hemofílica en la segunda década de vida 12,13 .…”
Section: Figuraunclassified
“…Hemarthrosis as the predominant presentation with most affected joint being knee joints were also found in Korean study 21 . However many other studies conducted in Netherlands, France and Spain showed ankle joint as mostly affected joints 22,23,24 .…”
Section: Clinical Manifestationmentioning
confidence: 99%